[(x^2 y^-2)^-1]^-1=

(1/x^2 y^-2)^-1=

(y^2/x^2)-1=

x^2/y^2

this solution is right according to the back of the book, are the steps also correct?

Printable View

- Apr 1st 2010, 05:48 PMdymand68simplification of exponential expression
[(x^2 y^-2)^-1]^-1=

(1/x^2 y^-2)^-1=

(y^2/x^2)-1=

x^2/y^2

this solution is right according to the back of the book, are the steps also correct? - Apr 1st 2010, 05:55 PMProve It
- Apr 1st 2010, 05:59 PMdymand68
ty.........so the correct order of operations starts with the negative exponent OUTSIDE the brackets?